Molecule template method for precise synthesis of Mo-based alloy clusters and electrocatalytic nitrogen reduction on partially reduced PtMo alloy oxide cluster. (December 2020) - Guo, Xu; Li, Xiangyan; Li, Yongcheng; Yang, Jiarui; Wan, Xin; Chen, Linyun; Liu, Jieyuan; Liu, Xiaofang; Yu, Ronghai; Zheng, Lirong; Shui, Jianglan
Abstract: Alloy clusters are attractive electrocatalysts that have adjustable activity through the synergistic effects of alloy components. However, the synthesis of atomically-precise alloy clusters is still a challenge. Here, we report a molecular template method in which phosphomolybdic acid adsorbs foreign noble metal ions, and then anneals into a series of Mo-based alloy oxide clusters (PtMo, IrMo, AuMo and PdMo), where oxygen is the terminal oxygen outside the cluster. The as-prepared alloy clusters have tunable atomic ratio and uniform size around 1 nm. Taking PtMo clusters as an example, their electrocatalytic nitrogen reduction reaction (NRR) has been investigated in depth. Among all compositions, PtMo-6 cluster (Pt:Mo atomic ratio 1:2) exhibits the highest NRR activity with a Faradaic efficiency of 14.37% and a NH3 yield rate of 65.3 μg h −1 mg −1 cat. in 0.1 M KOH, surpassing the known Mo-based catalysts. The combination of operando X-ray absorption spectroscopy and DFT calculations reveals that the oxide cluster in working state is the partially reduced. An unusual synergy is discovered, namely that Pt acts as a proton donor, providing *H to promote the hydrogenation of N2 on the adjacent Mo atom. This work provides a simple and universal method for the precise synthesis of alloy clusters and new guidance for designing highly efficient NRR catalysts. Graphical abstract: A molecule template method is developed to prepare Mo-based alloy clusters (PtMo, IrMo, AuMo and PdMo) with uniform particle size of 1–2 nm and controllable atomic ratio. Among all PtMo compositions, PtMo-6 cluster exhibits the highest electrocatalytic activity towards nitrogen reduction reaction. The combination of X-ray absorption spectroscopy and DFT calculations reveals the synergistic mechanism of NRR on PtMo-6 clusters, that is, Pt acts as a proton donor, providing *H (* represents active site) to promote the hydrogenation of N2 on nearby Mo atoms. Image 1 Highlights: A molecule template method is developed to prepare Mo-based alloy clusters. Partially oxidized PtMo cluster exhibits high electrocatalytic activity towards nitrogen reduction reaction. Operando observation of nitrogen reduction reaction on PtMo cluster by X-ray absorption spectroscopy. An unusual synergy is discovered, that is, Pt providing *H to promote the hydrogenation of N2 on Mo.